VARIASI INTERSPESIFIK JULANG (AVES: BUCEROTIDAE) INDONESIA BERDASARKAN GEN CYTOCHROME-B DNA MITOKONDRIA - Jarulis Jarulis; Dedy Duryadi Solihin; Ani Mardiastuti; Lilik Budi Prasetyo (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Genetic information of Indonesian hornbills (Julang) is still limited. We sequenced the cytochrome b gene of three hornbill species (Rhyticeros undulatus, R. plicatus, and Aceros cassidix) to explore their genetic variation, distance, and phylogenetic. Nine blood samples for Cyt b from three hornbill species were isolated with Dneasy® Blood and Tissue Kit base on Spin-Column Protocol, Qiagen. SNP, genetic distance, and phylogeny were calculated by MEGA 6.0 software. This study was found variations in the Cyt b gene sequence (849 bp) between three species Indonesian Julang. Rhyticeros undulatus had the most SNP compared to R. plicatus and Aceros cassidix. Substitution of synonyms is more common than substitution of synonyms and transition substitution frequency tends to be much higher than transversion substitution. The three species of Indonesian Julang were markedly separate with an average genetic distance of 5.25%. and separated with the outgroup species at a genetic distance of 9.43%. Cytochrome b sequence genes from these three hornbill species are novel for identifying and classifying hornbills, and could be applied to prevent illegal poaching and conservation management in Indonesia.